KESENJANGAN PERSEPSI PADA BPK RI DAN KPK TERHADAP KEAHLIAN AUDITOR FORENSIK - Imam Prayogo; Abdul Rohman (Jurnal Proaksi, 2020)
This study is aimed to examine the expectation gap between BPK RI and KPK about expertise of forensic auditors. The expertise of forensic auditors can to mind from deductive analysis, critical thinking, unstructured problem solving, investigative flexibility, analytical proficiency, oral communication, written communication, specific legal knowledge and composure. This study was held in government Republic Indonesia firms Jakarta. In this study data applied with survey of BPK RI and KPK in Jakarta. Respondents in this study are 33 BPK and 11 KPK. Data analysis method applied in this Independent sample T for hypothesis H1, H2, H3, H4, H5, H6, H7, H8 dan H9. Before testing the hypothesis, all questioners were testing by validity and reliability anlysis. The result of the validity and reliability show that all data is valid and reliable. The result of the study shows that there is expectation gap between BPK RI and KPK, in critical thinking (H2) and specific legal knowledge (H8). So, from this study the researcher concludes that there is perception difference between BPK RI and KPK about expertise of forensic auditors at deductive analysis (H1), unstructured problem solving (H3), investigative flexibility (H4), analytical proficiency (H5), oral communication (H6), written communication (H7), and composure (H9). The expectation gap between BPK RI and KPK about expertise of forensic auditors. Keywords: forensic auditors, expectation gap, BPK RI and KPK